2008
DOI: 10.1359/jbmr.071009
|View full text |Cite
|
Sign up to set email alerts
|

Complete Volumetric Decomposition of Individual Trabecular Plates and Rods and Its Morphological Correlations With Anisotropic Elastic Moduli in Human Trabecular Bone

Abstract: Introduction: Standard morphological analyses of trabecular architecture lack explicit segmentations of individual trabecular plates and rods. In this study, a complete volumetric decomposition technique was developed to segment trabecular bone microstructure into individual plates and rods. Contributions of trabecular typeassociated morphological parameters to the anisotropic elastic moduli of trabecular bone were studied. Materials and Methods: Seventy-one human trabecular bone samples from the femoral neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
258
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 217 publications
(276 citation statements)
references
References 33 publications
(91 reference statements)
11
258
1
6
Order By: Relevance
“…Previous studies using ITS analyses have demonstrated plate-like trabeculae to be the predominant contributor to mechanical competence of trabecular bone, and mechanical loading was mainly sustained by axially aligned trabeculae (17)(18). In accordance with the observations from femoral neck, tibia and vertebral body, we also found that pBV/TV correlated with axial elastic moduli as strongly as the BV/TV of the intertrochanteric trabecular bone.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies using ITS analyses have demonstrated plate-like trabeculae to be the predominant contributor to mechanical competence of trabecular bone, and mechanical loading was mainly sustained by axially aligned trabeculae (17)(18). In accordance with the observations from femoral neck, tibia and vertebral body, we also found that pBV/TV correlated with axial elastic moduli as strongly as the BV/TV of the intertrochanteric trabecular bone.…”
Section: Resultssupporting
confidence: 90%
“…We developed individual trabecula segmentation (ITS)-based morphological analysis, which resolved threedimensional (3D) trabecular bone image into individual trabeculae and provided explicit morphological evaluation for trabecular plates and rods. We have shown that trabecular plates and rods of different orientations had distinct roles in mechanical properties and failure mechanisms of trabecular bone (17)(18)(19). Also, ITS analysis has revealed the key differences between Caucasian American and Chinese American skeleton, demonstrating that higher plate/rod ratio accounted for reduced fracture risk in Chinese Americans in spite of similar aBMD (20).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…37 Isotropic material behavior was assumed, while cortical and trabecular bone are anisotropic. 38,39 As such, the model only reflected changes in stiffness as related to changes in bone architecture for these simplified loading conditions. For this comparative study, however, this was considered sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, additional factors, such as degree of mineralization, preexisting microdamage, and collagen cross-link profile may also play a role, yet the contribution of these factors to human trabecular bone mechanical properties remains incompletely understood.…”
mentioning
confidence: 99%